Perceptions of fishers in the Mutiara Indah Teritip Joint Business Group (KUB) on the Role of the Food, Agriculture, and Fisheries Agency (DP3) in East Balikpapan District, Balikpapan City - Tinambunan, Febriani; Sugiharto, Eko; Abdusysyahid, Said (Faculty of Fisheries and Marine Science, Mulawarman University, 2025)
Although fisheries institutions have developed, most remain small-scale operations managed traditionally, with weak management practices and limited access to information and technology. Understanding community perceptions is therefore essential. This study aims to examine fishers’ perceptions, both cumulatively and partially, within the Joint Business Group (Kelompok Usaha Bersama/KUB) Mutiara Indah Teritip regarding the role of the Food, Agriculture, and Fisheries Agency (Dinas Pangan, Pertanian dan Perikanan/DP3) in East Balikpapan District, as well as to identify the challenges faced by DP3 in this area. The research was conducted from September 2024 to May 2025 in East Balikpapan District, Balikpapan City. A total of 17 respondents were selected using purposive sampling. The results showed that the cumulative perception score of fishers in KUB Mutiara Indah Teritip regarding the role of DP3 reached 40.18, which falls within the range of 35.02–45.00 and is categorized as high. Similarly, the partial perception scores were also categorized as high, with indicator values as follows: program development for fishing activities (8.29), policy formulation for fisheries (8.35), supervision of fishing permits (8.41), guidance and training for fishers (7.88), and the application of fishing technology (7.24).